(untitled) (Asian Journal of Medical and Biological Research, 2021)
Coronavirus disease (COVID-19) is an infectious disease caused by the SARS-CoV-2 virus. Most people infected with the virus will experience mild to moderate respiratory illness and recover without requiring special treatment. However, some will become seriously ill and require medical attention. The virus after first identification on December 2019 in Wuhan, China spreads very fast all over the world including Bangladesh. To reduce the risk of COVID-19 transmission among medical students, teachers and staff, Ministry of Health and Family Welfare of Bangladesh government implemented home quarantine on first year MBBS students of 2020-21 session and ordered to begin online classes. A cross-sectional study was designed to assess the usage of smart phone in each positive and negative ways among students. Randomly 196 students completed an internet form (mean age 19±2 years). The questionnaire contains socio-economic, academic, quarantine connected data and smartphone usage. The majority of the participants (41.33%) assured that the usage of smartphone has been multiplied to eight to 12 hours per day. Many demographic and quarantine factors are assessed e.g. students’ gender, the sector of study additionally to the situation of quarantine (urban, rural) and also the speed of internet speed there showed statistically important associations with smartphone addiction throughout the quarantine. Smartphones are both a curse and a boon to the newer generation as a great way of getting used for education and entertainment purposes, conjointly influences a lot of sick habits within the first year MBBS students like looking adult sites or being obsessed on social or other websites. This study shows the use of smart phone in by the first year medical students of Sir Salimullah Medical College, Dhaka, Bangladesh in both positive and negative ways that also reflects the other first year medical students of 2020-21 session in Bangladesh. Asian J. Med. Biol. Res. 2021, 7 (3), 284-291